(untitled) (Annals of Medical Research, 2024)
Aim: Hashimoto’s thyroiditis (HT), the leading cause of hypothyroidism in developed nations, is an autoimmune condition characterized by the progressive destruction of the thyroid gland through various cell- and antibody-mediated immune mechanisms. C-reactive protein-to-albumin ratio (CAR) is a known inflammatory marker easily obtained from a routine blood test. In this context, this study aims to investigate the efficacy of CAR instead of conventionally used thyroid antibodies in predicting the diagnosis and prognosis of HT. Materials and Methods: The participants in this prospective cross-sectional study were adults aged 18 years and above diagnosed with Hashimoto’s thyroiditis (HT), seeking medical care at the Internal Medicine and Family Medicine Departments of Recep Tayyip Erdoğan University Training and Research Hospital in Rize, Turkey, during the period from April to July 2022. An age- and gender-matched control group was created from healthy individuals who applied to the outpatient clinics for routine check-ups. The patient and control groups were compared based on C-reactive protein (CRP), hemoglobin, and albumin serum levels of free triiodothyronine (FT3), free thyroxine (FT4), and thyroid stimulating hormone (TSH). Results: The patient and control groups comprised 142 HT patients and 62 healthy individuals. CRP level and CAR value were significantly higher. However, albumin and hemoglobin levels were significantly lower in the patient group than in the control group. [1.5 (0.4-5.6) mg/dL vs. 0.98 (0.3-2.6) mg/dL, p<0.001; 58 (11.5-193.1) vs. 29.5 (8.1-72.2) p<0.001; 2.9 (2.1-4.1) g/dL vs. 3.3 (2.3-4.2) g/dL, p<0.001; and 12±1.1 g/L vs. 12.7±1.760 g/L, p=.005; respectively]. The multivariate analysis revealed CRP, CAR, albumin, FT3, and hemoglobin as significant predictors of HT, with CAR being the most promising one among them [Odds Ratio (OR): 1.11, 95% confidence interval (CI): 1.38-1.19, p=0.003]. Conclusions: This study’s findings indicated that CAR is an easily measurable, reliable, and cost-effective marker of HT that can be used as an alternative to conventional thyroid antibodies in primary care centers.